SISTEM PAKAR UNTUK DIAGNOSIS PENYAKIT AUTOIMUN MENGGUNAKAN METODE FORWARD CHAINING - Wendra, Yumai; Safaria, Sayendra; Rahim, Radiyan (Smart Education, 2024)
Abstract: The need for technology in the health sector continues to grow and is increasingly important to improve the quality of medical services, operational efficiency, and accessibility for patients. The application of technology in the health sector can have a significant impact in terms of increasing access to medical services, the effectiveness of diagnosis and treatment, and the management of medical information and data. Autoimmune disease is a condition in which the immune system attacks the human body. Autoimmune occurs when the immune system is disrupted and cannot maintain the stability of the body's condition, so it attacks healthy body tissue by considering it a foreign object that needs to be destroyed. Diagnosing autoimmune diseases is often challenging because the symptoms can vary greatly and resemble other diseases. Treatment usually focuses on managing symptoms and suppressing the immune response to reduce damage to body tissue. The purpose of this study is to create an expert system that helps the public in early detection and recognizing types of autoimmune diseases based on several symptoms experienced by patients. The results of this study are the creation of a diagnostic system for autoimmune diseases which is expected to facilitate the process of diagnosing autoimmune diseases.Keyword: forward chaining; expert system; autoimmune. Abstrak: Kebutuhan teknologi dalam dunia kesehatan terus berkembang dan semakin penting untuk meningkatkan kualitas pelayanan medis, efisiensi operasional, serta aksesibilitas bagi pasien. Penerapan teknologi dalam dunia kesehatan dapat memberikan dampak signifikan dalam hal peningkatan akses terhadap layanan medis, efektivitas diagnosis dan perawatan, serta pengelolaan informasi dan data medis. Penyakit autoimun adalah kondisi di mana sistem kekebalan tubuh menyerang tubuh manusia. Autoimun terjadi ketika sistem kekebalan tubuh mengalami gangguan dan tidak dapat menjaga kestabilan kondisi tubuh, sehingga menyerang jaringan tubuh yang sehat dengan menganggapnya sebagai benda asing yang perlu dihancurkan. Diagnosa penyakit autoimun sering kali menantang karena gejalanya bisa sangat bervariasi dan menyerupai penyakit lain. Perawatan biasanya berfokus pada mengelola gejala dan menekan respon imun untuk mengurangi kerusakan pada jaringan tubuh. Adapun tujuan dari penelitian ini adalah membuat sistem pakar yang membantu masyarakat dalam mendeteksi secara dini dan mengenali jenis penyakit autoimun berdasarkan beberapa gejala yang dialami oleh pasien. Hasil dari penelitian ini terciptanya sistem diagnosa untuk penyakit autoimun yang diharapkan dapat mempermudah proses diagnosis penyakit autoimun.Kata kunci: forward chaining; sistem pakar; autoimun.